The pan-European population distribution across consistently defined functional urban areas - Kurt Schmidheiny; Jens Suedekum (European Regional Science Association (ERSA), 2015)
We analyze the first data set on consistently defined functional urban areas in Europe and compare the European to the US urban system. City sizes in Europe do not follow a power law: the largest cities are ?too small? to follow Zipf?s law.
Keywords: R11; R12; 330; City size distributions; Zipf's law; functional urban areas; urban systems